2020
DOI: 10.1155/2020/7646384
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Uric Acid Concentration and Its Change with Cardiovascular Death and All-Cause Mortality

Abstract: Objective. There is no consensus on the role of abnormal uric acid (UA) levels in the prognosis of patients undergoing hemodialysis. We therefore aimed to investigate the effects of changes in UA concentration on the risk of all-cause death and cardiac death in such patients. Method. In this retrospective cohort study, patients admitted to two hemodialysis centers performing maintenance hemodialysis (MHD) in Wuhan First Hospital and Fourth Hospital Hemodialysis Center from January 1, 2007, to October 31, 2017,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Previous studies report that low and high UA levels are correlated with increased mortality with approximately 1.5~5.0 times higher risk. Notably, 1 mg/dL UA levels increase is related to 3 times higher risk, and a U-shaped association occurs between SUA levels and adverse health outcomes ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies report that low and high UA levels are correlated with increased mortality with approximately 1.5~5.0 times higher risk. Notably, 1 mg/dL UA levels increase is related to 3 times higher risk, and a U-shaped association occurs between SUA levels and adverse health outcomes ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gerber et al (15) reported that the development of cardiovascular events was higher in those with low uric acid levels. Li et al (24) and Dong et al (25) reported in their study that hemodialysis patients with low uric acid levels were associated with high risk for cardiovascular mortality and all-cause mortality. Aker Karagöz et al (26) reported that there was no relationship between uric acid level and the development of CVD in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indices of visit-to-visit SUA variability include the coefficient of variation (CV), SD, average real variability (ARV), and variability independent of the mean (VIM). The CV was calculated as (SD/mean) × 100% [24]. The ARV calculated as the average absolute difference between successive measurements [25].…”
Section: Measurement Of Sua Change and Variabilitymentioning
confidence: 99%